2018
DOI: 10.1039/c7mh00699c
|View full text |Cite
|
Sign up to set email alerts
|

Rationally designed meta-implants: a combination of auxetic and conventional meta-biomaterials

Abstract: Rationally designed meta-implants were found to create compression along both of their contact lines with the surrounding bone, thereby decreasing the chance of bone–implant interface failure (Hoffman's criterion) and wear particle-induced osteolysis, and improving bone ingrowth.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
163
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 267 publications
(163 citation statements)
references
References 21 publications
0
163
0
Order By: Relevance
“…Other potential applications of mechanical metamaterials which makes use of its topological flexibility, size effects, and material constituents includes the creation of architected thermal heat exchangers and insulators, photonic crystals with unique optical properties, phononic crystals with tailorable bandgaps for acoustic cloaking, battery electrodes with optimized topology for electron transport, electrochemical and mechanical properties, and bio‐scaffolds or meta‐biomaterials, which involves the rational design of an optimized combination of mechanical, mass transport and biological properties to enhance tissue regeneration . Recently, microlattices for tunable electromagnetic shielding has also been reported …”
Section: Utilizing Architecture Size Effect and Mechanismmentioning
confidence: 99%
See 2 more Smart Citations
“…Other potential applications of mechanical metamaterials which makes use of its topological flexibility, size effects, and material constituents includes the creation of architected thermal heat exchangers and insulators, photonic crystals with unique optical properties, phononic crystals with tailorable bandgaps for acoustic cloaking, battery electrodes with optimized topology for electron transport, electrochemical and mechanical properties, and bio‐scaffolds or meta‐biomaterials, which involves the rational design of an optimized combination of mechanical, mass transport and biological properties to enhance tissue regeneration . Recently, microlattices for tunable electromagnetic shielding has also been reported …”
Section: Utilizing Architecture Size Effect and Mechanismmentioning
confidence: 99%
“…Owing to the relieved pressure on the swelling area, the hierarchical design could potentially be used in skin grafts as well . Other recent progresses include a rationally‐designed hip implant (Figure d, e) which combines both auxetic (negative Poisson's ratio) and conventional honeycomb (positive Poisson's ratio) structures to decrease the probability of a bone implant interface failure by minimizing the chance of wear particles entering the enclosed space (Hoffman's criterion) and mechanically stimulating bone growth to enhance fixation . They made use of SLM to 3D print these hybrid meta‐implants with biomedical‐grade titanium alloy Ti6Al4V‐ELI.…”
Section: Typical Examples Of Mechanical Metamaterialsmentioning
confidence: 99%
See 1 more Smart Citation
“…74 These properties make PEO highly suitable for the modification of AM meta-biomaterials, that are currently under development and may in the future significantly improve the fixation of bone scaffolds and orthopedic implants. 75 Assigning antibacterial properties to these highly porous structures will be crucial to fight off IAI. Thus far, some studies have indicated that the enormous surface area of AM porous biomaterials allows for enhanced antibacterial performance of biofunctionalized implants bearing Ag NPs alone 8 or in combination with antibiotics.…”
Section: View Article Onlinementioning
confidence: 99%
“…For example, electromagnetic metamaterials can have a negative refractive index (which causes incident radiation to refract in the opposite direction to a conventional material) . Mechanical metamaterials can have a negative Poisson's ratio (where a material expands laterally as it is stretched longitudinally, rather than contracts) . Analogously, a biological metamaterial results in an unnatural biological response.…”
Section: Introductionmentioning
confidence: 99%